1998
DOI: 10.1046/j.1365-2265.1998.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile secretion of ACTH and cortisol in premenopausal women: effect of obesity and body fat distribution

Abstract: This study demonstrates that in premenopausal women, obesity, particularly the visceral phenotype, is associated with several abnormalities of ACTH pulsatile secretion, particularly in the morning. On the contrary, no major differences were present in either blood concentrations, diurnal rhythm or secretory pattern of cortisol between obese and controls. The responses to meals seem to indicate a much more rapid cortisol response after lunch in women with visceral obesity and a reduced activation of the hypotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 33 publications
(38 reference statements)
7
38
0
Order By: Relevance
“…The CRH-ACTH system appears to be activated in obesity, although the number of studies in which spontaneous plasma ACTH secretion patterns were analyzed is rather limited (10,12,33,39). Elevated CRH in obese subjects is likely responsible for the increased ACTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The CRH-ACTH system appears to be activated in obesity, although the number of studies in which spontaneous plasma ACTH secretion patterns were analyzed is rather limited (10,12,33,39). Elevated CRH in obese subjects is likely responsible for the increased ACTH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…To represent the individually secreted amount of cortisol (Peeke & Chrousos 1995, the resulting area under the curve (AUC) of the morning values (n=4, from waking to 0930 h) was taken and expressed as a concentration. This procedure is valid for both sexes (Pasquali et al 1998).…”
Section: Measuring Devicesmentioning
confidence: 99%
“…For instance, the study of HPA axis ultradian rhythms in premenopausal, viscerally obese women revealed several abnormalities of ACTH pulsatile secretion (increased pulse frequency and reduced pulse amplitude) which were not accompanied by abnormal mean ACTH concentrations in peripheral blood (Pasquali et al, 1998). Another example is obstructive sleep apnoea; in a recent study, the deconvolution analysis of secretory pulses in the 24h systemic GC profiles of untreated patients revealed longer duration of ACTH and cortisol pulses compared to the same patients when they had been successfully treated with continuous positive airway pressure therapy (Henley et al, 2009b).…”
Section: Altered Hpa Rhythmicity In Stressful Conditions and Human Pamentioning
confidence: 99%